Analisis Kepuasan Pasien sebagai Mediasi Pengaruh Kualitas Pelayanan Kesehatan terhadap Citra Rumah Sakit Umum Daerah (RSUD) Arifin Achmad Pekanbaru - Marzaweny, Diskha; Hadiwidjojo, Djumilah; chandra, teddy (Jurnal Aplikasi Manajemen, 2012)
The purpose of this research is to investigate the relationship between healthcare quality, patient satisfaction and the image of Arifin Achmad Pekanbaru General Hospital, and the mediating effect of patient satisfaction. Healthcare quality in this research was measured using Servqual model from Parasuraman et al. Sample in this research were 100 inpatients who are undergoing treatment at the Arifin Achmad Pekanbaru General Hospital at the time of data collection / interviews conducted in July 2011, with the following criteria: a) Patients had undergone inpatient treatment for a minimum of 2 days. b) Patients was conscious and able to communicate properly. c) Patients are not children. d) Patients are not hospital employees or their families. Hypotheses testing in this research were analysed using Path Analysis. The results indicate that healthcare quality has a positive and significant impact on patient satisfaction and the hospital image. Patient satisfaction has also significant impact on hospital image. Moreover, patient satisfaction appears to play mediating role in relationship between healthcare quality and the image of Arifin Achmad Pekanbaru General Hospital.